2022
DOI: 10.1080/22221751.2022.2136535
|View full text |Cite
|
Sign up to set email alerts
|

Omicron infections profile and vaccination status among 1881 liver transplant recipients: a multi-centre retrospective cohort

Abstract: A wave of Omicron infections rapidly emerged in China in 2022, but large-scale data concerning the safety profile of vaccines and Coronavirus disease 2019 (COVID-19) infection features in liver transplant (LT) recipients have not been collected. Therefore, the aim of this study was to assess the protectiveness and safety profile of the inactivated vaccines in LT patients against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant infections. A multi-centre retrospective study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…Although these characteristics set the sample apart from most vaccinated LT recipients, such differences may be attenuated by evidence of the lower effectiveness of vaccines in this population [ 10 , 11 ]. Moreover, the results may still represent the fraction of patients with incomplete or absent vaccination, knowingly those in which more deaths and severe cases currently occur (and those in which more concerns are raised regarding modifications to immunosuppression) [12] , [13] , [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Although these characteristics set the sample apart from most vaccinated LT recipients, such differences may be attenuated by evidence of the lower effectiveness of vaccines in this population [ 10 , 11 ]. Moreover, the results may still represent the fraction of patients with incomplete or absent vaccination, knowingly those in which more deaths and severe cases currently occur (and those in which more concerns are raised regarding modifications to immunosuppression) [12] , [13] , [14] .…”
Section: Discussionmentioning
confidence: 99%
“…The primary composite outcome was liver function abnormality. Liver function abnormality was defined as an increase over the upper limit of the normal range 5 , 27 , 29 , 30 within the week of COVID-19 diagnosis in any of the following parameters: alanine aminotransferase (ALT, >50 U/L), aspartate aminotransferase (AST, >35 U/L), Îł-glutamyl transpeptidase (GGT, >60 U/L), alkaline phosphatase (ALP, >135 U/L), total bilirubin (TBIL, >21 U/L), or direct bilirubin (DBIL, >5.1 U/L). The secondary outcome was viral shedding duration, which was defined as the number of days from the date of the first positive PCR test result to the date of the first negative PCR test result, followed by consecutive negative results.…”
Section: Methodsmentioning
confidence: 99%
“…The secondary outcome was viral shedding duration, which was defined as the number of days from the date of the first positive PCR test result to the date of the first negative PCR test result, followed by consecutive negative results. 29 Data including demographics, medical history, liver function, and viral shedding duration were extracted from the electronic medical records in the relevant registries.…”
Section: Methodsmentioning
confidence: 99%
“…Although strict epidemic prevention measures have led to a decline in the number of COVID-19 infections, China made adjustments to its epidemic prevention policy on December 7, 2022, resulting in a surge in cases from December 2022 to January 2023. During this period, the primary variant circulating in China was Omicron [ 16 ]. Previous studies have shown a significantly increased risk of adverse outcomes and a mortality rate close to 20% in patients with concurrent AP and COVID-19 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%